2012
DOI: 10.1136/bjsports-2012-090953
|View full text |Cite
|
Sign up to set email alerts
|

Gluteal muscle activity and patellofemoral pain syndrome: a systematic review

Abstract: Objective There is growing evidence to support the association of gluteal muscle strength deficits in individuals with patellofemoral pain syndrome (PFPS) and the effectiveness of gluteal strengthening when treating PFPS. In additiona, an impressive body of work evaluating gluteal electromyography (EMG) has recently emerged, further supporting the importance of gluteal muscle function in PFPS. This systematic review synthesises these EMG findings in order to better understand the role of gluteal muscle activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
98
2
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(106 citation statements)
references
References 47 publications
(64 reference statements)
2
98
2
4
Order By: Relevance
“…Investigators, who investigated different individuals with anterior knee pain and pain free ones, reported difference in medial femoral rotation to be 12.2-13° (15,16). Changes in femoral rotation might be caused by quadriceps muscle atrophy (17) or increased femoral anteversion (18). Another possible explanation for medial femoral rotation is a "screw home" mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Investigators, who investigated different individuals with anterior knee pain and pain free ones, reported difference in medial femoral rotation to be 12.2-13° (15,16). Changes in femoral rotation might be caused by quadriceps muscle atrophy (17) or increased femoral anteversion (18). Another possible explanation for medial femoral rotation is a "screw home" mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, females with PFP have been reported to demonstrate delayed onset and decreased duration of gluteus medius activity during running and stair ascent. 2,8,11,36 A recent systematic review 4 similarly concluded that there is evidence for delayed onset and decreased duration of gluteus medius activation during running and stair negotiation in females with PFP, but, interestingly, there is little evidence to support alterations in the amplitude of gluteus medius activation. Further, increased onset latencies and reduced duration of activation of the gluteus medius have also been correlated with increased hip frontal plane motions during running in females with PFP.…”
Section: T T Discussion: While Changes In Hip Mechanicsmentioning
confidence: 99%
“…Additionally, three reviews were identified as high quality meta-analysis or systematic reviews of RCTs [11,38,39] whilst the other two [12,13] as high quality systematic reviews of case control or cohort studies. Therefore, the level of the first three reviews was found to have high methodological level (8)(9)(10)(11) in the AMSTAR tool whilst the two reviews of case control or cohort studies had moderate methodological level (4-7 in the AMSTAR tool). Only the reviews from Heintjes et al [38] and Collins et al [11] reported more than 20 items from the PRISMA checklist (24 and 26 out of 27 correspondingly) whilst the other three reported 14 or less.…”
Section: Exercise Treatmentmentioning
confidence: 99%
“…Lately, researchers and decision makers have started to confront an overflow of reviews [5,6]. From July 2012 to March 2013 the British Journal of Sport Medicine alone has published 4 systematic reviews on PFPS [7][8][9][10]. Because there are several reviews on similar topics and because it is likely for reviews to be of varied scope and quality, a growing interest of systematic review of reviews (RoR) has been called for [3].…”
mentioning
confidence: 99%